Storming a castle : a maze adventure - White, Graham, 1953- (Washington, D.C. : National Geographic, 2002)
By solving a maze puzzle, the reader can help a twelve-year-old boy to assist his father, a knight in an army fighting a cruel and greedy king, and learn about medieval castles.
"Ages 8-12"--Cover p. [4].
Includes index.
5.2
3-6
3-6
Keywords: Maze puzzles -- Juvenile literature; Castles -- Juvenile literature; Maze puzzles; Puzzles; Castles; Maze puzzles; Puzzles; Castles